RESPON PERTUMBUHAN KAPULAGA LOKAL (Amomum compactum Soland Ex. Maton) DAN KAPULAGA SABRANG (Elettaria cardamomum (L.) Maton Var. Mysore) TERHADAP CEKAMAN KEKERINGAN - Mohamad Nurzaman; Sri Ratu Dewi Pridani; Tia Setiawati (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Drought stress is an inhibiting factor in agricultural, one of the effort to overcome these problems is to use varietiesof plants that are tolerant to drought stress. Cardamom is a plant of the Zingiberaceae which is able to grow indrought stress. This research aims to obtain the growth response of local Javanese cardamom (A. compactum)and true cardamom (E. cardamomum) and to obtain the kind of cardamom that is tolerant to drought stress. Thisresearch was conducted using experimental method and completely randomized design (CRD) with 2 x 4 factorialand four repetitions. The first factor was the variation of field capacity (K) and the second factor was the type ofcardamom (J). Parameters measured include the increase of plant height (cm), plant weight (grams), leaf area(cm2), number of leaves, leaf chlorophyll content (mg / l), and leaf proline content (ppm). The data was analysedusing analysis of variance (ANOVA) and Duncan test α 5%. Results showed that local Javanese cardamom (A.compactum) has better growth response and was more tolerant to drought stress compared to true cardamom (E.cardamomum). Keywords: drought stress, local Javanese cardamom (A. compactum), true cardamom (E. cardamomum).